(untitled) (The Review of Diabetic Studies, 2025)
Background: Pediatric autoimmune diseases provide a significant challenge in modern medicine due to their complex and diverse nature, often impacting several organ systems and challenging conventional diagnostic approaches. Aim: This study aims to examines the diagnostic framework of pediatric autoimmune illnesses, emphasizing the necessity of a multidisciplinary and imaging focused strategy to facilitate early diagnosis, optimize care, and improve outcomes for affected children. Method: This 12-month multi-focused longitudinal cohort study includes quantitative clinical and laboratory assessments at baseline, 6 months, and 12 months, including readmission rates, immunological tests, and disease-directed imaging. The qualitative component includes parent, doctor, and nurse interviews and standardized questions on care quality, communication, and satisfaction. Data analysis uses repeated measures ANOVA for quantitative assessments and reliability analysis for qualitative responses, with a significance level of p < 0.05. Clinical outcomes and satisfaction metrics are triangulated to assess interdisciplinary care. Ethics were approved by institutional review boards. Results The research demonstrated notable advancements in pediatric autoimmune illnesses after a 12-month follow-up, including improvements in clinical, immunological, and psychosocial metrics. Laboratory findings demonstrated elevated complement levels and reduced autoantibodies, indicating successful immunological regulation. Clinically, there were reductions in hospital readmissions, enhanced treatment responses, increased quality of life, and decreased depression ratings. The research underscored the importance of multidisciplinary treatment, highlighting effective team communication and parental satisfaction. An analysis of 50 radiological cases demonstrated the effectiveness of particular imaging techniques, improving diagnostic precision and patient results. Conclusion In conclusion, early and integrated imaging within a multidisciplinary framework significantly improved the treatment of pediatric autoimmune disorders.